POLITIK HUKUM PENGATURAN KEUANGAN PARTAI POLITIK DI INDONESIA - Ratna Kartika Indraswari; Martina Fina (Universitas Muhammadiyah Jember, 2020)
This study aim to analyse the three problems related to political party financial matter. First, how does the statutory regulates the political party finance in Indonesia? Second, what issues must be regulated in statutory regarding political party finance. Third, what is the ideal model for political party finance regulation for Indonesia?This research is a socio-legal research. In addition to examined the statutory regarding political party, the researcher also examined the legislation proccess transcript related to the statutory. In other words, the researcher sought to explore the background of the statutory provision formulation during its legislation process. Based on research variation according to F. Sugeng Istanto, this research may be categorised as literature research on the content of statutory law and applied law, qualitative and prescriptive. In this research, the statutory-approach used to understand the UU No. 2 Tahun 2011; historical-approach used to understand the legislation proccess transcript related to the statutory; comparative-approach used to understand the political parties financial regulations in Germany and the United States; while conceptual-approach used to understand the concept of popular sovereignty, representative democracy, freedom of assembly, political parties concept, the concept of political party accountability and transparency, the anatomy of political party law, and the politics of law concerning political party financial regulation. The data used in this research are secondary data such as statutory text, legislation proccess transcript, books, journals, articles, scripts from the internet, and dictionaries.From the analysis, thre researcher concludes that: First, the political party financial regulation in Indonesia adopted a permissive model, in which, there are very high freedom for political parties, very loose demands of financial transparency and accountability, weak public supervision and obscure sanctions; Second, the law must regulate the mechanism of public funding for political party, obligations to reveal to source and amount of donations, standards for financial reports, obligation to submit financial statements periodically to supervisory agendies, obligation related the periodically financial audit by external professional auditors, donations cap, prohibitions of certain donations source, sanctions for violations. Third, the ideal political party finance regulation model for Indonesia is by combining the demands of transparency, demands of periodically financial audit by external professional auditors, ban on foreign source donations and non taxable entities source donations, reasonable restriction on nominal donation per person per year, enforcement of Election Commission and Election Supervisory Board through strong authorization to supervise and to impose severe administrative sanctions, the public funding given as a partial reimbursement for the previous year operating cost provided that the party has complied the financial transparency and accountability obligations.